GAMBARAN PERAN ORANGTUA DALAM MEMBERIKAN PENDIDIKAN SEKS PADA REMAJA DIFABEL DI SLB - Maria Tobing, May Ave; Zulfitri, Reni; Dewi, Ari Pristiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Parents play an important role in providing sexual education to disabled youth considering the number of crimes or acts of sexual violence in adolescents are expected to prevent unexpected pregnancies and prevent deviant sexual behavior. The important role of parents is very important because sex is an important and personal problem. This study aims to describe the role of parents in providing sex education to disabled youth in Pekanbaru Pembina Negeri SLB. This research is a quantitative descriptive method research. This study uses univariate analysis. Sampling uses stratified random sampling with the number of respondents 65 parents. The instrument used is a questionnaire on the role of parents in providing sexual education. The results of this study indicate the role of parents as educators in the good category as many as 62 people (95.4%); the role of parents as decision makers with good categories as many as 50 people (76.9%); the role of parents as supervisors in the good category is 39 people (60%); the role of parents as counselors in the good category is 55 people (84.6%). The advice given is that parents are expected not to consider taboo and provide open communication to adolescents so that they can enhance the role of parents as educators, decision makers, supervisors, and counselors. Keywords: Disabled youth, The role of parents, Sexual education